Fast and continuous microorganism detection using aptamer-conjugated fluorescent nanoparticles on an optofluidic platform - Chung, Jinyang; Kang, Joon Sang; Jurng, Jong Soo; Jung, Jae Hee; Kim, Byoung Chan (ELSEVIER ADVANCED TECHNOLOGY, 2015)
Fast and accurate pathogen detection in aquatic environments is challenging in many biomedical studies and microbial diagnostic applications. In this study, we developed a real-time, continuous, and non-destructive single cell detection method using target specific aptamer-conjugated fluorescent nanopartides (A-FNPs) and an optofluidic particle-sensor platform. A-FNPs selectively bound to the surfaces of target bacteria (Escherichia coli) and labeled them with high affinity and selectivity so that target bacteria can be countable particles in an optofluidic particle-sensor. A-FNP-labeled target bacterial complexes were detected by the optofluidic particle-sensing system, which provides rapid and continuous single-cell detection. A-FNPs selectively bound to E. coli with a dissociation constant of 0.83 nM, but did not bind Enterobacter aerogenes or Citrobacter freundii strains, which lacked affinity for the aptamer used. We demonstrated that our optofluidic device achieves a detection throughput of similar to 100 particles per second with high accuracy (similar to 85%) in detecting single bacterial cells conjugated with A-FNPs. This approach can be immediately extended to the real-time, high-throughput detection of other microorganisms such as viruses that are selectively conjugated with A-FNPs. Collectively, these data suggest that optofluidic systems are widely applicable for the fast and continuous detection of microbial cells. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: IN-VITRO SELECTION; ESCHERICHIA-COLI; BACTERIAL-CELLS; DRINKING-WATER; RNA; MOLECULES; BINDING; QUANTIFICATION; SPECIFICITY; ANTIBODIES